2022
DOI: 10.32598/ijt.16.1.854.1
|View full text |Cite
|
Sign up to set email alerts
|

The Nephroprotective Effect of Clove Oil (Oleum Caryophylli) Against Levofloxacin Toxicity in Rats

Abstract: Background: Levofloxacin is a fluoroquinolone antibiotic that has broad-spectrum antimicrobial activity, but it may induce kidney dysfunction. Clove oil (Oleum caryophylli) has antioxidant properties that may alleviate levofloxacin toxicity. This study aimed to examine the protective effect of clove oil on levofloxacin-induced nephrotoxicity in rat animal models. Methods: A total of 24 male rats were divided into 6 groups. One group did not receive levofloxacin to serve as the control. The treatment groups rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The clove oil protected both the renal function and structures and the protective effect was comparable to that of curcuma extract (hepaprotective agent) treatment. The study found that the administration of clove bud extract for 90 days at doses up to 1 g/kg did not generate observable clinical signs of injury to the liver or kidneys in wistar rats and therefore oral administration of clove oil proved safe at doses under 1 g/kg in animal models [28].…”
Section: Scientific Evidences Of Clove L Antibacterial Activitymentioning
confidence: 94%
“…The clove oil protected both the renal function and structures and the protective effect was comparable to that of curcuma extract (hepaprotective agent) treatment. The study found that the administration of clove bud extract for 90 days at doses up to 1 g/kg did not generate observable clinical signs of injury to the liver or kidneys in wistar rats and therefore oral administration of clove oil proved safe at doses under 1 g/kg in animal models [28].…”
Section: Scientific Evidences Of Clove L Antibacterial Activitymentioning
confidence: 94%